Patterns of contestation across EU parliaments: four modes of inter-parliamentary relations compared. Issue 2 (23rd February 2022) - Crum, Ben
Abstract: Studies of political contestation of EU decision making usually focus on the division lines in the European Parliament and, to a lesser extent, the Council of Ministers. This article seeks to broaden the analysis of the contestation of EU politics by conceptualising EU contestation across the EU's 'multilevel parliamentary field'. It distinguishes three ideal-typical structures of contestation – national, inter-institutional, and transnational contestation – and hypothesises that the more institutionalised the mode of EU decision making, the more likely it is that contestation takes place along transnational lines. The article then draws on the empirical literature on multilevel parliamentarism to assess the plausibility of this hypothesis for four modes of EU decision making: EU legislation, executive decisions, policy coordination and institutional design. Finding the hypothesis broadly confirmed, the article concludes that, if the supranational implications of EU decision making are to be appreciated, also less institutionalised decision-making modes require some form of transnational contestation.